Responses and coping mechanism among diabetic foot ulcer patients: A Qualitative Study - Jiu, Cau Kim; Parliani; Aryadi, Deni (YCAB Publisher, 2025)
Background: Diabetic foot ulcers (DFUs) pose serious threats to the physical and psychological well-being of affected individuals, often requiring prolonged and multidimensional care. These wounds not only impact mobility and quality of life but also present emotional burdens that influence treatment adherence. Objective: This qualitative study aims to explore the lived experiences of patients with DFUs by examining their understanding of the condition, emotional and behavioral responses, and the coping strategies employed during wound management. Method: A qualitative approach was applied through semi-structured interviews with a purposively selected sample of patients diagnosed with DFUs. Data were analyzed thematically to identify patterns in patient narratives related to adaptation, support, and self-care. Results: The analysis revealed key themes, including emotional distress, adaptive coping mechanisms, and the role of healthcare providers in facilitating patient education. Participants expressed the need for personalized support and continuous guidance to maintain effective wound care and psychological resilience. Conclusion: Enhancing patient-centered care, improving health literacy, and integrating emotional support into routine treatment are essential in optimizing outcomes for individuals living with DFUs. Keywords: diabetic foot; self-care; quality of life; healthcare delivery; adaptation